THE EFFECT OF WORK ENVIRONMENT, MOTIVATION, AND WORK SATISFACTION ON EMPLOYEE PERFORMANCE: A CASE STUDY OF ONE OF THE REGIONAL-OWNED COMPANIES IN MEDAN - Jesicha Onasis Br. Sembiring (Laboratorium Riset Ekonomi, 2023)
This study aims to examine and analyze the effect of work environment, motivation and work satisfaction on employee performance at the Head Office of one of the regional-owned company in Medan. 137 people were chosen as the sample using a stratified random sampling technique out of 209 people of the population. This descriptive quantitative study applied Multiple Linear Regression Analysis as the analytical technique with a significance level of 5%. The results of this study has revealed that simultaneously work environment, motivation and work satisfaction have a significant effect on the employee performance of the Head Office of one of the regional-owned company in Medan. The partial test shows that each of the work environment, motivation and work satisfaction has a positive and significant effect on the employee performance of the Head Office of one of the regional-owned company in Medan. Since the score of determinant coefficient (R2) is 51.4%, the employee performance variable can be explained by the work environment, motivation and work satisfaction variables while the remaining 48.6% can be explained by other factors which were not examined in this